Strategies for Introducing the Cultural Values of Gresik Embodied in Damar Kurung: A Study on Early Childhood - Ubaidillah, Ubaidillah; Nisa, Aini Farkhatun; Amaliyah, Fara Abidatul; Saidah, Syafa’atul Nur; Wulandari, Ajeng; Nathania, Aprilia Dini Nasywa; Imamah, Roisatul (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to introduce the cultural values of Gresik through Damar Kurung, a cultural icon, to early childhood students as part of preserving local wisdom and shaping the character of future generations. The research employs a descriptive qualitative method using observation, interviews, and documentation. The subjects are 20 children aged 3-4 years at Taman Pengasuhan Anak (TPA) Harmoni in Gresik Regency, selected using purposive sampling. The results reveal that cultural introduction strategies involving direct and audiovisual exposure to Damar Kurung, coloring activities, and practicing traditional and religious values effectively enhance children's cultural understanding and fine motor skills. Approximately 70% of participants showed expected developmental progress in recognizing cultural values, including religiosity, tradition, social interaction, and education. This research concludes that utilizing local art forms like Damar Kurung as educational media provides enjoyable and meaningful learning experiences supporting young children's character development. Such strategies expand cultural awareness, foster an appreciation for local arts, and inspire a commitment to preserving traditions among younger generations.